Copper diffusion in ZnS thin films - Bacaksiz, E; Dzhafarov, TD; Novruzov, VD; Öztürk, K; Tomakin, M; Küçükömeroglu, T; Altunbas, M; Yanmaz, E; Abay, B (WILEY-V C H VERLAG GMBH, 2004)
Diffusion of Cu in ZnS thin films was investigated in the temperature range 80-400degreesC using the energy-dispersive X-ray fluorescence (EDXRF) technique. ZnS thin films were deposited by spray pyrolysis on a glass substrate. The temperature dependence of the Cu diffusion coefficient is described by the equation D = 1.4 x 10(-10) exp [-(0.18 eV)/kT]. It is shown that diffusion doping of n-type ZnS by Cu is accompanied by a significant increase in resistivity and a slight decrease in the band gap of the ZnS films. The observed results are attributed to the migration of Cu in polycrystalline ZnS films by means of diffusion both along grain boundaries and into grains. (C) 2004 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: OPTICAL-PROPERTIES; CU; CDS; Materials Science; Physics